Pengaruh Pendekatan Problem Solving terhadap Kreativitas Belajar Matematika Siswa Kelas XI Man 1 Sleman - Paldi; Nanang Khuzaini (Mataram University, 2026)
This study aims to examine the effect of a problem-solving approach on students' mathematical learning creativity at MAN 1 Sleman, while comparing its efficacy against conventional teaching methods in the context of Function Transformation topics. Employing a quantitative approach, this study adopted a pretest-posttest control group experimental design. Data were gathered using a test instrument specifically designed to measure students' mathematical learning creativity. The collected data were then analyzed using paired-sample t-tests and independent-sample t-tests at a 5% significance level. The findings indicate that the problem-solving approach significantly influences the mathematical learning creativity of Grade XI students at MAN 1 Sleman when studying Function Transformations. This significant impact is demonstrated by a substantial increase in the mean creativity score from 13.33 to 19.57, yielding a significance value of Sig. < 0.05. Conversely, the conventional method did not yield a statistically significant effect on students' learning creativity. Furthermore, although the independent-sample t-test results revealed no statistically significant direct difference between the two methods (Sig. > 0.05) the problem-solving approach practically demonstrated a superior internal impact. This is evidenced by a far higher total increase in the mean creativity score (6.24) compared to that generated by the conventional method (0.73).